Combining FLASH and spatially fractionated radiation therapy: The best of both worlds. (October 2022) - Schneider, Tim; Fernandez-Palomo, Cristian; Bertho, Annaïg; Fazzari, Jennifer; Iturri, Lorea; Martin, Olga A.; Trappetti, Verdiana; Djonov, Valentin; Prezado, Yolanda
Highlights: Advantages and current limitations of FLASH and spatially fractionated radiotherapy (SFRT). Similarities and differences between FLASH and SFRT. Devices for simultaneous application of FLASH and SFRT: current status and perspectives. Abstract: FLASH radiotherapy (FLASH-RT) and spatially fractionated radiation therapy (SFRT) are two new therapeutical strategies that use non-standard dose delivery methods to reduce normal tissue toxicity and increase the therapeutic index. Although likely based on different mechanisms, both FLASH-RT and SFRT have shown to elicit radiobiological effects that significantly differ from those induced by conventional radiotherapy. With the therapeutic potential having been established separately for each technique, the combination of FLASH-RT and SFRT could therefore represent a winning alliance. In this review, we discuss the state of the art, advantages and current limitations, potential synergies, and where a combination of these two techniques could be implemented today or in the near future.